Pengaruh Pendidikan Kesehatan Terhadap Pengetahuan Tentang Perawatan Payudara Masa Nifas Pada Ibu Hamil Trimester III Di Puskesmas Pajang Surakarta - Wibowo, Agung, Dr. Faizah Betty Rahayuningsih, M.Kes (2017)
Introduction Breast Care choose a lot of benefits including avoiding sore nipples or abrasions, prevent infection and facilitate breast milk after childbirth expenses. Knowledge of puerperal women are very important in the formation of breast care measures so that later the fulfillment of exclusive breastfeeding was no trouble. The purpose of this study was to determine the knowledge of third trimester pregnant women about breast care before and after health education and to determine whether there is influence of health education on knowledge about breast care during childbirth in pregnant women in the third trimester Pajang Surakarta Health Center. This research method is a pre-experimental research design with one group pre-post test design. This research was conducted at the health center Surakarta Showcase in February 2017. Samples taken as many as 33 third trimester pregnant women with purposive sampling technique. The instrument used was a questionnaire knowledge of breast care. Test to determine the data analysis using non-parametric Wilcoxon test. The results showed an average knowledge of pregnant women before being given health education on breast care amounted to 61.09 and the average knowledge of pregnant women after health education given at 79.56 with a significant value of 0.000 or p <0.05. The limitation in this study is to provide health education less than the maximum because the location is a bit crowded. Places provision of health education in the waiting room Health Center Pajang poly KIA and conducted during business hours health center, so that the concentration of respondents in the pregnant women receive less than the maximum material. The conclusion shows the influence of health education on breast care during childbirth to pregnant women in the third trimester Pajang Surakarta Health Center. Suggestions for health centers to incorporate health education program periodically or sustainable in the treatment of breast health center in pregnant women can improve the quality of health services in health centers and education institutions are expected to improve and add to the literature on a deeper study on breast care during childbirth.